2005
DOI: 10.1128/jcm.43.8.3851-3859.2005
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of the SpirochetesBorrelia parkeriandBorrelia turicataeand the Potential for Tick-Borne Relapsing Fever in Florida

Abstract: Isolates of Borrelia turicatae, Borrelia parkeri, and the Florida canine borrelia (FCB) were examined to further phylogenetically characterize the identities of these spirochetes in the United States. DNA sequences of four chromosomal loci (the 16S rRNA gene, flaB, gyrB, and glpQ) were determined for eight isolates of B. turicatae and six isolates of B. parkeri, which grouped the spirochetes into two distinct but closely related taxa (>98% sequence identity) separate from Borrelia hermsii. The FCB was clearly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 63 publications
(53 reference statements)
3
149
0
1
Order By: Relevance
“…parkeri and B. turicatae represent closely related spirochetes in the United States that are suspected to cause tickborne relapsing fever in humans (9). Although epidemiological evidence is strong for B. turicatae as a cause of human infections, isolation of B. turicatae and B. parkeri from human patients has not yet been documented (45). In this study, we have identified a receptor from B. parkeri for CFH and CFHR-1, two key soluble-phase inhibitory molecules of the alternative complement pathway, and we showed that binding of CFH to BpcA permits resistance to complement-mediated killing by NHS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…parkeri and B. turicatae represent closely related spirochetes in the United States that are suspected to cause tickborne relapsing fever in humans (9). Although epidemiological evidence is strong for B. turicatae as a cause of human infections, isolation of B. turicatae and B. parkeri from human patients has not yet been documented (45). In this study, we have identified a receptor from B. parkeri for CFH and CFHR-1, two key soluble-phase inhibitory molecules of the alternative complement pathway, and we showed that binding of CFH to BpcA permits resistance to complement-mediated killing by NHS.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the availability of genetic tools and genome sequence data, discrimination between closely related species causing relapsing fever infections among humans is now feasible. Although B. hermsii has been isolated frequently from humans, direct evidence for B. parkeri and B. turicatae being pathogenic to humans is still missing (4,44,45).…”
mentioning
confidence: 99%
“…Genomic DNA samples from Legionella isolates (Table 1, codes 2 to 18) were examined for lpg2644 and mip homologues by Southern blot analysis under low-stringency conditions (72,76). The hybridization probes were designed from conserved regions of the respective genes and amplified from genomic DNA of L. pneumophila Lp02 with a PCR digoxigenin (DIG) probe synthesis kit (Roche Applied Science, Laval, QC, Canada) using primers 10 and 11 and primers 12 and 13 ( Table 3).…”
Section: Methodsmentioning
confidence: 99%
“…We studied 17 Borrelia isolates that originated primarily from ticks or humans in North America (Table 1) (Porcella et al, 2005;Schwan et al, 2005). All relapsing fever spirochaetes were cultured in modified Kelly's medium (complete BSK-H) (Sigma-Aldrich) supplemented with 12% rabbit serum.…”
Section: Borrelia Strains and Cultivationmentioning
confidence: 99%